Modern Approaches To Imaging And Liver Function Assessment In Biliary Obstruction - Nurmurzayev, Zafar (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Obstructive jaundice remains one of the most significant challenges in modern abdominal surgery, being accompanied by progressive impairment of bile outflow, toxic hepatocellular injury, and the development of hepatic failure. Early and accurate diagnosis of the level and cause of biliary obstruction determines the timeliness and effectiveness of treatment, reducing mortality and postoperative complications. Modern radiological methods — ultrasound (US), multislice computed tomography (MSCT), magnetic resonance cholangiopancreatography (MRCP), and endoscopic retrograde cholangiopancreatography (ERCP) — allow noninvasive and highly informative assessment of both anatomical and functional changes in the biliary system and liver parenchyma, making them indispensable tools in comprehensive diagnosis.